Psychological Trauma Reflected in B.Rangarao’s Dalit Short Story Death of a Rich Man - Suryakant Parkale; Vishnu Rajput (Emerging Trends in Languages, 2023)
In the growing expansion of marginalized literature, B.Rangarao’s short story collection “Desperate Men and Women: Ten Dalit Short Stories from India” has been greatly applauded by the readers as it brilliantly exposed the trauma of both men and women of Dalit community in autocratic conditions in India. In Dalit writing Rangrao’s contribution gave fresh look especially to the short story genre as it is based on the revolutionary ideas of Shahu Phule and Dr Ambedkar. As a writer he follows the literary path of Baburao Bagul, Anna Bhau Sathe, Waman Howal and Shankarrao Kharat and enriched the tradition of Dalit writing. The present short story entitled as “Death of a Rich Man” shows the discriminatory system based on age old orthodox traditions and customs that subordinates and even humiliates both men and women of Dalit community in the village setup. In addition to that it focuses on multiple issues related to the Dalit’s survival like poverty, untouchability, struggle for survival, and gender disparity. The present research paper humbly concentrates on the character of Sattya who represents the Mahar community whose life has been preoccupied with adverse conditions at personal as well as socio-cultural level, which is why he suffers from psychological trauma in the story. The character of Sattya has been studied under the light of psychological trauma theory and holds castiest society responsible for it.
Keywords: Dalit writing; Marginalized; discriminatory system; psychological; trauma